Pengaruh Harga, Promosi Dan Inovasi Produk Terhadap Kesuksesan Usaha Mikro Kecil Menengah Bidang Kuliner Di Kecamatan Ploso Kabupaten Jombang - Akhmad Azim Shiraj; Agus Widarko; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstract This study aimed to determine the influence of prices, promotion and product innovation on the success of micro, medium and small businesses in the food industry in Ploso County, Jombang Regency. The sample used in this study is 85 UMKM in the culinary field. different labels for price, promotion and product innovation have a significant influence on the success of Micro, MSMEs in the culinary sector of Ploso County. , Regency of Jombang. Keyword: Price, Promotion, Product Innovation, Success, UMKM